Thermal degradation kinetic, electrical and dielectric behavior of brush copolymer with a polystyrene backbone and polyacrylate-amide side chains/ nanographene-filled composites - Biryan, Fatih; Demirelli, Kadir (Elsevier, 2019)
A brush copolymer having polystyrene backbone and flexible PA-amide (polyacrylate-amide) brushes that exhibit thermoplastic elastomer property was synthesized, and brush copolymer composites with nanographene in various ratios were prepared. The thermal properties of the macroinitiator, brush copolymer and composites were investigated using differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA). The activation energy (E-a) of thermal decomposition of brush copolymer/6wt% nanographene was estimated by the Flynn-Wall-Ozawa method, and the average activation energy value for the 0.1-0.7 conversion was estimated as being 141.7 kJ/mol. Electrically conducting nanographene-based brush copolymer composites were produced. DC and AC electrical conductivity and dielectric properties of permittivity of nanographene-based brush copolymer composites were investigated. Further, the activation energy profile of different nanographene/brush copolymer composites were determined by measuring DC conductivity of individual composite materials. A heterojunction diode made from the polymer nanographene composites were magnified on a p-type Si substrate using a hydro/solvo thermal method. The polymer composite/p-Si thin film heterojunction diode properties were studied using current-voltage (I-V) and capacitance-voltage (C-V) analysis. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Electrical properties; Kinetic; Brush copolymer; Nanographene; Composite